S2k guideline diagnosis and treatment of carbon monoxide poisoning S2k-leitlinie diagnostik und therapie der kohlenmonoxidvergiftung - Jüttner, Björn; Busch, Hans Jörg; Callies, Andreas; Dormann, Harald; Janisch, Thorsten; Kaiser, Guido; Körner-Göbel, Hella; Kluba, Karsten; Kluge, Stefan; Leidel, Bernd A.; Müller, Oliver; Naser, Johannes; et al. (GMS German Medical Science, 2021)
Carbon monoxide (CO) can occur in numerous situations and ambient conditions, such as fire smoke, indoor fireplaces, silos containing large quantities of wood pellets, engine exhaust fumes, and when using hookahs. Symptoms of CO poisoning are nonspecific and can range from dizziness, headache, and angina pectoris to unconsciousness and death. This guideline presents the current state of knowledge and national recommendations on the diagnosis and treatment of patients with CO poisoning. The diagnosis of CO poisoning is based on clinical symptoms and proven or probable exposure to CO. Negative carboxyhemoglobin (COHb) levels should not rule out CO poisoning if the history and symptoms are consistent with this phenomenon. Reduced oxygen-carrying capacity, impairment of the cellular respiratory chain, and immunomodulatory pro-cesses may result in myocardial and central nervous tissue damage even after a reduction in COHb. If CO poisoning is suspected, 100% oxygen breathing should be immediately initiated in the prehospital setting. Clinical symptoms do not correlate with COHb elimination from the blood; therefore, COHb monitoring alone is unsuitable for treatment management. Especially in the absence of improvement despite treatment, a reevaluation for other possible differential diagnoses ought to be performed. Evidence regarding the benefit of hyperbaric oxygen therapy (HBOT) is scant and the subject of controversy due to the heterogeneity of studies. If required, HBOT should be initiated within 6 h. All patients with CO poisoning should be informed about the risk of delayed neurological sequelae (DNS).
CRIS-Team Scopus Importer:2025-02-03
Keywords: Carbon monoxide poisoning; CO hemoglobin; Delayed neurological sequelae (DNS); Etiology; HBOT; Hyperbaric oxygen therapy; Initial in-hospital care; Oxygen breathing; Prehospital management; Prevention; Rehabilitation